NOTES ON RESUPINATE HYMENOMYCETES-I On Pellicularia Cooke - DONK, M. A. (REINWARDTIA, 1954)
The author concludes that Pellicularia Cooke is to be regarded as the name of an inseparable mixtum compositum (nomen confusum) and hence as illegitimate (impriorable).He believes that, apart from a hypothetical gelatinous medium,Cookes original material consisted of the combination of the vegetative hyphae of a resupinate hymenomycete and the spores of a pervading imperfect fungus. If one of these constituent elements were to be selected as type, the choice would be the spores rather than the vegetative byphae selected by Rogers.